Proximate and sensory analysis of cooked Red Rice (Raktashali) at room temperature (International Journal of Food and Nutritional Sciences, 2024)
The study aimed to develop and standardize a wholesome and traditional Indian preparation using red rice (Raktashali), focusing on its proximate and sensory analysis at room temperature. The objective was to create a nutritious and innovative food product rooted in Ayurvedic literature